Effects of climatic change on soil processes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
Effects of expected climate change on soil processes, a workshop organized by UNEP, CTA and the International Society of Soil Science (ISSS) in Nairobi from 12-14 February 1990. This was followed (15-17 February) by an ad hoc consultation meeting on 'Asse